“Rescued Women”: Early Pentecostal Responses to Sex Trafficking - Isgrigg, Daniel D. (Pneuma, 2022)
This article traces the history of early pentecostal responses to sex trafficking and the related issue of prostitution. It documents the stories of Pentecostal Rescue missions recorded in pentecostal papers such as The Bridegroom’s Messenger, Apostolic Faith, Weekly Evangel, and the Pentecostal Holiness Advocate. This study explores pentecostal views of society and culture as well as rhetoric about trafficked women, especially the concepts of victimhood, guilt, and culpability for “fallen women.” It demonstrates how ministry to trafficked women positively and negatively shaped pentecostal attitudes toward women and dress in the pentecostal tradition.